Islam : an advanced introduction - Tottoli, Roberto (New York : Routledge, 2020)
"Exploring complex relations between Muslim visions and critical stances, this textbook is a compact introduction to Islam, dealing with the origins of its forms, from early developments to contemporary issues, including religious principles, beliefs and practices. The author's innovative method considers the various opposing theories and approaches between the Islamic tradition and scholars of Islam. Each topic is accompanied by up-to-date bibliographical references and a list of titles for further study, while an exhaustive glossary includes the elementary notions to allow in-depth study. The first part outlines the two founding aspects, the Qur'an and Prophet Muhammad, highlighting essential concepts, according to Islamic religious discourse and related critical issues. The emergence of the religious themes that have characterised the formation of the Sunni Islam are explored in terms of historical developments. The second part, on contemporary Islam, examines the growth of Islam between the end of the Middle Ages and the beginning of modern age. Advanced readers, already familiar with the elementary notions of Islam and religious studies will benefit from the volume that explores the development of religious discourse in a historical perspective. This unique textbook is a key resource to post-graduate researchers and academics interested in Islam, religion and the Middle East"--
Introduction -- 1. Muhammad -- 2. The Qur'an -- 3. Islam and Muslims in history -- 4. A tradition between unity and diversity -- 5. The Islamic community -- 6. Modern and contemporary Islam -- Glossary -- Bibliography: Further Reading -- Index of names.
Includes bibliographical references and index.
Keywords: Islam -- History